Plant-soil feedbacks - Veen, Ciska (Henry Stewart Talks, 2020)
The definition of plant-soil feedback, Mechanisms of plant-soil feedback, Soil biodiversity, Plant abundance and plant diversity, Diversity-productivity relationships, Temporal dynamics and succession, Plant invasion, Aboveground-belowground interactions, Plant soil feedback under global change